Analisis manajemen komplain di Pondok Pesantren Islamic Center Bin Baz Putra - Widiyanto; Gusmen, Islah (TA`DIBUNA, 2024)
This study aims to identify the types of complaints, their causes, and the implementation of complaint management at the Islamic Center Bin Baz Boarding School for Boys in Yogyakarta. Using a qualitative descriptive method, data were collected through documentation, observation, and in-depth interviews. The findings revealed nine types of complaints, including cleanliness, security, food quality, health, complaint services, extracurricular activities, other needs, facilities and infrastructure, as well as laundry services. Complaint handling is managed by the Mudir, Head of the Boarding Division, Chief Caregiver, and Caregivers through management functions: planning, organizing, actuating, and monitoring. The study concludes that the handling of complaints from parents and students at this boarding school has been conducted effectively, although there is no officially issued Standard Operating Procedure (SOP) from the Mudir. This is evidenced by the low number of parents transferring their children to other schools and the relatively stable number of students each year. AbstrakPenelitian ini bertujuan mengidentifikasi jenis komplain, faktor penyebabnya, dan implementasi manajemen komplain di Pondok Pesantren Islamic Center Bin Baz Putra Yogyakarta. Menggunakan metode deskriptif kualitatif, data dikumpulkan melalui dokumentasi, observasi, dan wawancara mendalam. Hasil penelitian menunjukkan terdapat 9 jenis komplain, meliputi kebersihan, keamanan, kualitas makanan, kesehatan, layanan keluhan, kegiatan intrakurikuler, kebutuhan lainnya, sarana dan prasarana, serta laundry. Penanganan komplain dilakukan oleh Mudir, Kepala Divisi Kepesantrenan, Ketua Pengasuhan, dan Pengasuh melalui fungsi manajemen: perencanaan, pengorganisasian, penggerakan, dan pengawasan. Penelitian menyimpulkan bahwa penanganan komplain wali santri dan santri di pondok pesantren ini sudah berjalan baik meskipun belum ada Standar Operasional Prosedur (SOP) resmi dari Mudir. Hal ini tercermin dari minimnya wali santri yang memindahkan anaknya ke pesantren lain serta jumlah santri yang stabil setiap tahun.